Peran Pelatihan dan Sertifikasi dalam Meningkatkan Kompetensi SDM Perbankan Syariah: Indonesia - Irvan Dian Budiarto (Cashless : Journal of Sharia Finance and Banking, 2023)
Islamic banking in Indonesia is growing rapidly in line with increasing public awareness of the sharia-based financial system and regulatory support from the government. However, this growth faces challenges in the availability of human resources (HR) who have competencies in accordance with sharia principles and modern banking practices. This study aims to analyze the role of training and certification in improving the competence of Islamic banking human resources. The method used is a literature study by examining various secondary sources, such as academic journals, industry reports, and Islamic banking regulations. The results of the study show that systematic training and certification programs can improve the understanding of the workforce of sharia principles, increase compliance with regulations, and strengthen the competitiveness of the sharia banking industry. In conclusion, investment in the training and certification of Islamic banking human resources is urgently needed to ensure the sustainability and credibility of the sector. Synergy between the government, banking institutions, and educational institutions needs to be strengthened to expand access to sharia-based human resource development programs. Keywords : Training, Certification, Competence, Human Resources and Sharia Banking